'The Health-Secure Partnership': Study protocol for the development of a school- & community-based intervention for promoting healthy nutrition among rural adolescents in The Gambia. - Haddy Jallow-Badjan; Anne-Marie Bagnall; Tanefa A Apekey; Haddy Tunkara Bah; Haddy Crookes; Ramatoulie E Janha; Fatoumatta Kassama; Hassan Njie; Oritseweyinmi Erikowa-Orighoye; Thomas Senghore; Tayamika Zabula; Maria J Maynard; et al. (PLoS ONE)
Introduction Interventions addressing malnutrition (under- and overnutrition) among adolescents have not been developed in The Gambia. We aim to coproduce the first phase of 'The Health-Secure Partnership' (HSP) - an innovative multicomponent intervention for adolescents in rural areas of The Gambia. Inference drawn from existing evidence and public contribution suggest that the future intervention would ideally involve nutrition-specific components coupled with changes to wider school and community contexts, delivered in partnerships between schools and local communities. Methods The design of HSP is underpinned by health promoting school and community centred approaches, informed by a systems-thinking lens. The project activities will be conducted in three linked stages. Stage 1: Current nutrition-related activities and environments will be observed in four rural Gambian schools, their local village communities, and one additional village which does not have a school. Around 50 key stakeholders (such as teachers, parents, community members, and wider systems stakeholders) will complete questionnaires on their views on the current nutrition-related context and systems, cultural norms, and actions needed to address adolescent malnutrition. Focus groups and interviews will then be conducted with approximately 70 adolescent girls and boys to understand their experiences and opinions about their intervention needs. Stage 2: Potential intervention components, session content and mode/s of delivery will be explored in meetings and workshops with the consortium and stakeholders (including adolescents) to achieve consensus on the intervention format. Examples of session content, and intervention resources will be made, and a community event held to see what the public think of the ideas and materials. Stage 3: A description of the intervention and a codesigned evaluation plan will be documented. Dissemination will include publications, presentations, song and drama to suit a range of audiences (adolescents and their communities, other stakeholders, academics, and policy makers). Discussion This study protocol presents our plans for the HSP intervention development project, addressing a critical gap in the evidence base. Findings will inform subsequent research phases exploring the feasibility and acceptability of the intervention among adolescents.